Stress ribbon and cable-supported pedestrian bridges - Strasky, Jiri (Ice Publishing, 2011)
This new and fully updated edition of Stress Ribbon and Cable-supported Pedestrian Bridges examines all aspects of the design of these structures. Starting with a brief history, the title describes structural types, addresses general design criteria, current technology, static and dynamic analysis and discusses the results of the static and dynamic loading tests.